2016
DOI: 10.5009/gnl15460
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 141 Expression Is a Potential Prognostic Marker of Biliary Tract Cancers

Abstract: Background/AimsIn recent years, a large number of micro-ribonucleic acids (miRNAs) have been identified as putative prognostic biomarkers for solid cancers because of their role in controlling the expression of oncogenes and tumor suppressor genes. The aim of this study was to verify the utility of miRNA 141 as a prognostic biomarker of biliary tract cancers.MethodsFrom June 2010 to June 2012, common bile duct cancer tissue samples and matched noncancerous tissues from the ampulla of Vater were obtained from p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Conversely, ectopic expression of miR200 family members in BTC cells reduced sphere formation, expression of CD133 as well as invasion rate, formation of metastases and triggering of EMT in vitro and in vivo, underlining the crucial role of the miR200 family, especially regarding EMT in BTC [16,17]. However, in contrast to these findings, over-expression of miR141 was found to be a predictor of poor prognosis and shorter disease-free and overall survival in another study, demonstrating that members of the miR200 family may act as both oncogenes and tumor suppressors in BTC [20]. …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, ectopic expression of miR200 family members in BTC cells reduced sphere formation, expression of CD133 as well as invasion rate, formation of metastases and triggering of EMT in vitro and in vivo, underlining the crucial role of the miR200 family, especially regarding EMT in BTC [16,17]. However, in contrast to these findings, over-expression of miR141 was found to be a predictor of poor prognosis and shorter disease-free and overall survival in another study, demonstrating that members of the miR200 family may act as both oncogenes and tumor suppressors in BTC [20]. …”
Section: Introductionmentioning
confidence: 99%
“…This is why the new prognostic markers for pancreatobiliary cancers are very important and essential to treat and follow up on the aggressive cancers. In this issue of Gut and Liver , Kim et al 4. suggested that miRNA 141 may be a valuable prognostic biomarker in patients with biliary tract cancer.…”
mentioning
confidence: 99%
“…In this issue of Gut and Liver , Kim et al . 4 suggested that miRNA 141 may be a valuable prognostic biomarker in patients with biliary tract cancer. The miRNA 141 highly overexpressed in malignant cholangiocytes was suggested as an important regulator of tumor cell proliferation in vitro and decreasing miRNA 141 overexpression may be useful to inhibit tumor progress in previous study.…”
mentioning
confidence: 99%